131k views
4 votes
I need help. I won't be able to get this!!!

I need help. I won't be able to get this!!!-example-1

2 Answers

5 votes

Answer:

D. No Solution

Explanation:

13(9−6x)=5−2x13(9-6x)=5-2x

Simplify 13⋅(9−6x)13⋅(9-6x).

Apply the distributive property.

13⋅9+13(−6x)=5−2x13⋅9+13(-6x)=5-2x

Cancel the common factor of 33

3+13(−6x)=5−2x3+13(-6x)=5-2x

Cancel the common factor of 33.

3−2x=5−2x3-2x=5-2x

Move all terms containing xx to the left side of the equation

Add 2x2x to both sides of the equation.

3−2x+2x=53-2x+2x=5

Combine the opposite terms in 3−2x+2x3-2x+2x.

3=53=5

Since 3≠53≠5, there are no solutions.

No solution

User Boris Gougeon
by
5.4k points
5 votes

Answer:

A

James King

Hope This Helped

Have A Great Day

User Bhavin Rana
by
5.9k points